MARKET MICROSTRUCTURE AND FINANCING EFFICIENCY IN MSMES IN INDONESIA: COMPARISON OF SHARIA AND CONVENTIONAL SECTORS - Harisandi, Prasetyo; Sari, Maya; Yulandri, Elsa (Finansha: Journal of Sharia Financial Management, 2023)
The objective of this research is to examine the financing efficacy and market microstructure of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Specifically, it compares the conventional sector with the sharia-compliant sector. This study employs Structural Equation Modeling with Partial Least Squares (SEM-PLS 4) to examine access to financing, utilization of collateral, and ability to pay with a sample of 132 MSMEs. The results of the study demonstrate distinct variations between conventional and sharia-compliant MSMEs, underscoring the influence of market microstructure elements on financial accessibility. SMBs that adhere to sharia law demonstrate, in particular, increased levels of access to capital and utilization of collateral. This research makes a valuable contribution to the comprehension of sectoral dynamics and provides policymakers, financial institutions, and MSMEs in Indonesia with practical implications.